2021
DOI: 10.3389/fnagi.2020.591737
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Obstructive Sleep Apnea, Its Treatment, and Alzheimer's Disease: Systematic Mini-Review

Abstract: Obstructive sleep apnea (OSA) and Alzheimer's disease (AD) are common in the elderly population. Obstructive sleep apnea that may cause significant changes in the cerebrospinal fluid β-amyloid and T-tau and/or P-tau protein levels is often identified as a risk factor for development of AD. Although the underlying mechanisms of AD are still not fully understood, a hypothesis associating OSA with AD has been already proposed. In this systematic mini-review, we first discuss the recent findings supporting the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Circadian rhythm disturbances have been suggested as biomarkers for clinical stage AD [43]. The ndings of our genetic analyses were highly consistent, generally supporting the observational positive associations between AD with insomnia [3] and snoring [44], and the negative associations with sleep duration [45]. We also observed AD was positively associated with napping (r g = 0.16, p = 1.61×10 − 2 ), but this signi cance disappeared after Bonferroni correction.…”
Section: Discussionsupporting
confidence: 83%
“…Circadian rhythm disturbances have been suggested as biomarkers for clinical stage AD [43]. The ndings of our genetic analyses were highly consistent, generally supporting the observational positive associations between AD with insomnia [3] and snoring [44], and the negative associations with sleep duration [45]. We also observed AD was positively associated with napping (r g = 0.16, p = 1.61×10 − 2 ), but this signi cance disappeared after Bonferroni correction.…”
Section: Discussionsupporting
confidence: 83%
“…Circadian rhythm disturbances have been suggested as biomarkers for clinical stage AD ( Liguori et al, 2020 ). The findings of our genetic analyses were highly consistent, generally supporting the observational positive associations between AD with insomnia ( Sadeghmousavi et al, 2020 ) and snoring ( Kuo et al, 2020 ) and the negative associations with sleep duration ( Lutsey et al, 2018 ). We also observed that AD was positively associated with napping ( r g = 0.16, p = 1.61 × 10 –2 ), but this significance disappeared after Bonferroni correction.…”
Section: Discussionsupporting
confidence: 79%
“…CPAP users had lower odds of incident diagnoses of AD (odds ratio [OR] = 0.78, 95% confidence interval [95% CI] = 0.69 to 0.89) and mild cognitive impairment (OR = 0.82, 95% CI = 0.66 to 1.02) [ 35 ]. A related systematic review indicated that receiving CPAP intervention for OSA treatment reduced the risk of AD [ 36 ]. Collectively, the results indicate that employing CPAP intervention to alleviate OSA symptoms and improve sleep quality can indirectly prevent neurodegenerative diseases by reducing neurochemical biomarker levels.…”
Section: Discussionmentioning
confidence: 99%